Accountability and review in the counter-terrorist state / Jessie Blackbourn, Fiona de Londras, Lydia Morgan. - Blackbourn, Jessie; De Londras, Fiona; Morgan, Lydia (Bristol University Press, 2020)
Counter-terrorism is now a permanent and sprawling part of the legislative and operational apparatus of the state, yet little is known about the law and practice of how it is reviewed, how effective the review mechanisms are, what impact they have or how they interact with one another. This book addresses that gap in knowledge by presenting the first comprehensive, critical analysis of counter-terrorism review in the United Kingdom, informed by exclusive interviews with policy makers, politicians, practitioners and civil society.